Cryptocurrency Risk Analysis During the Covid-19 Pandemic: Value at Risk (VaR) Approach - Desy Khairunnisa; Budi Purwanto; Wita Juwita Ermawati (IPB University, 2022)
The COVID-19 outbreak had a severe impact on almost all countries in the world. One aspect of concern during the pandemic is an investment. In this study, the GARCH model used to estimate Value at Risk (VaR) on cryptocurrency investments as a tolerable loss during the COVID-19 pandemic. Data in this study are ten cryptocurrencies with the largest capitalization. The observation period when WHO declared COVID-19 as a pandemic, namely on March 11, 2020 - June 11, 2020. From this study, the highest cryptocurrency VaR value is Crypto.com with an amount of 0,18214. It means that the maximum loss that an investor can tolerate with an investment of 500.000.000 for a 95 percent confidence level is 91.070.392.